Interdisciplinary approaches to zoonotic disease - Robin Goodwin; David Schley; Ka-Man Lai; Graziano M. Ceddia; Julie Barnett; NIgel Cook (MDPI AG, 2012)
Zoonotic infections are on the increase worldwide, but most research into the biological, environmental and life science aspects of these infections has been conducted in separation. In this review we bring together contemporary research in these areas to suggest a new, symbiotic framework which recognises the interaction of biological, economic, psychological, and natural and built environmental drivers in zoonotic infection and transmission. In doing so, we propose that some contemporary debates in zoonotic research could be resolved using an expanded framework which explicitly takes into account the combination of motivated and habitual human behaviour, environmental and biological constraints, and their interactions.